TR Locus Annotation and Characteristics of Rhinolophus ferrumequinum - Zhou, Hao; Ma, Long; Liu, Longyu; Yao, Xinsheng (Frontiers in Immunology, 2021)
T cell antigen receptors (TCRs) in vertebrate could be divided into αβ or γδ, which are encoded by TRA/D, TRG and TRB loci respectively. TCRs play a central role in mammal cellular immunity, which are functionally produced by rearrangement of V gene, D gene, J gene and C gene in the loci. Bat is the only mammal with flying ability, and is considered as the main host of zoonotic virus, which occupies an important position in the field of public health. At present, little is known about the composition of bat TRs gene. According to the whole genome sequencing results of the Rhinolophus ferrumequinum, and referring to the TR/IG annotation rules formulated by IMGT. We make a complete annotation on the TRA/D, TRG and TRB loci of the Rhinolophus ferrumequinum. A total of 128 V segments, 3 D segments, 85 J segments and 6 C segments were annotated, in addition to compared with the known mammalian, the characteristics of the TRs locus and germline genes of the Rhinolophus ferrumequinum were analyzed.